Tuesday

October 6, 2015
Posted by **Carrie** on Wednesday, February 15, 2012 at 9:28pm.

-2/3x + y = 2

2x - 3y = 6

So i put y= 2/3x into the second equation which looks like:

2x - 3(2/3x + 2) = 6

and then

2x-2x-6=6

So like everything cancels out? So then what do you put as the answer??

Thanks!

- Math -
**MIKE**, Wednesday, February 15, 2012 at 9:34pmso i think its

x=0

then solver y

2(0)-3y=6

y=-2

- Math -
**Carrie**, Wednesday, February 15, 2012 at 9:56pmoh, ok thanks!

- Math -
**MIKE**, Wednesday, February 15, 2012 at 10:01pmwelcome